The Study of Chok Mae Chaem’s Patterns for Applying Knitted - อินภักดี, จินตนา (Community and Social Development Journal, 2018)
The objectives of this research and development on the Mae Chaem weaving motif designs for knitting application were to examine the motif designs and identity of Mae Chaem hand-woven cotton in Mae Chaem District, Chiang Mai Province, to design the knitting designs based on the motif designs in order to add value to the knitting work according to the creative economy, and to test the knitting products by investigating levels of satisfaction of the target consumers. The population and sample groups included 1) ten villagers from Ban Rai Village # 10, Tambon Tha Pha, Mae Chaem District, by using the purposive sampling method to select those who could provide the information on the motif weaving patterns; 2) five village representatives to select the folk designs to be applied for knitting; 3) three experts to evaluate the knitting designs and the knitting manual; 4) twelve target members for the knitting experiment from the knitting manual; and 5) 100 target consumers for testing the knitting products. The research instruments were a semi-structured interview, a knitting design assessment, a knitting manual, a knitting manual assessment and a questionnaire. The quantitative data were statistically analyzed for percentage, mean, and standard deviation and the content analysis method was used to analyze the qualitative data. The analysis results revealed that the Mae Chaem designs are classified into four categories, namely idealistic, man and animal, flower, and daily-used utensil. There are two design aspects: lantern and coop. The identity of the weaving designs is in the shades of yellow, red and orange. The designs applied for knitting were Kut Khor Bet, Chiang Saen Hong Ploy, and Khan Sian Sam. The designs were of a lantern, but only its body and base were utilized to apply for the development of the knitted scarves by using a packaged computer program to design. Knitting patterns were printed on and embroidered. When the knitted scarves were assessed by the three experts, it was found that the average scores were 4.17, and the knitting manual assessed it was found that the average score were 4.19, at a high level. When the experimental manual was implemented and assessed by students at San Kam Phaeng School, the average scores were 4.53, at the highest level. When the products were tested with the target consumers, the average scores of their satisfaction level were 4.42, at a high level. The designs with which they were most satisfied, ranked from high to low, were Khan Sian Sam, with the average scores of 4.47; Chiang Saen Hong Ploy, with the average scores of 4.42; and Kut Khor Bet, with the average scores of 4.38 respectively. Conclude that knitted scarf products can add value to the knitting work according to the creative economy. Which is based defined criteria it was found that the average scores were more 4.00. It was suggested by the consumers that knitting materials be diverse. For instance, bamboo tissue-based wool should be used to make scarves since it does not irritate the skin and can add more value to the products than acrylic wool.